In vivo toxicity study of phage lysate in chickens - Oliveira, A. (2009)
1. Bacteriophage (phage) crude lysate of Gram-negative bacteria often contains bacterial debris, including lipopolysaccharides found in the outer membrane of the cell wall, which are potentially toxic. 2. In this study, an in vivo evaluation of the toxicity of a suspension of three phages to control pathogenic Escherichia coli strains in poultry was performed. 3. Eighteen commercial layers, 7 weeks old, were intramuscularly injected with phage lysate (8.21x10 4 Endotoxin Units/dose). The control group was injected with sterile Luria Bertani (LB) broth. 4. Bird prostration and decrease in body weight gain and water intake per gram of body weight were observed only on the day of the inoculation in the challenged group. Over the following 6 d, no differences were observed in the chickens’ activity. 5. These results support the view that phage crude lysate carrying endotoxins are not toxic for chickens.